MENGEMBANGKAN KAMPUNG PENGRAJIN TOSAN AJI DI DESA PASIR WETAN, BANYUMAS - Wijarnako, Beny R.; Wakhudin, Wakhudin; Aryani, Ine Kusuma (Jurnal Pengabdian Indonesia (JPI), 2025)
This Science and Technology for the Community aims to develop the Tosan Aji Craftsman Village in Pasir Wetan Village, Banyumas. Building a craftsman village is increasingly urgent to preserve the ancestral heritage of Khudi, a tool and heirloom typical of the Banyumas people, so that it continues to exist, even to be developed as an economically valuable heritage. This Science and Technology for the Community uses a participatory action research approach by involving craftsmen, community leaders, and the village government. Data collection techniques were carried out using field observation techniques and in-depth interviews with craftsmen. The community also conducted workshops and mentoring training. The IbM results show that, to revive the Tosan Aji MSME, craftsmen need training in contemporary tosan aji making techniques that combine contemporary equipment with modern equipment. Craftsmen need assistance in creating e-commerce and digital promotional content. It is possible for these Tosan Aji craftsmen to become more advanced if their lives are packaged in an educational tourism package that includes a tosan aji making workshop, even the creation of a mini museum.